Sensitivity of hybrid plasmons in nanowire based triangular/square clusters to surrounding dielectric environment - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2014)
This paper presents investigation of plasmonic properties of coupled metal nanowires arranged to form the cluster of triangular or square configuration. Plasmon resonances of such structures embedded into dielectrics with different dielectric permittivity are studied. The main goal of the paper is to validate true potential of plasmon nanowire-based structures in sensing applications and reveal optimized configurations with narrowband plasmonic resonances and enhanced sensitivity.
Keywords: Plasmons; nanowires